The advantages and disadvantages of using higher education students' Artificial intelligence. (Comprehensive Journal of Science, 2026)
As artificial intelligence becomes more common in our daily lives, its effect on education calls for both enthusiasm and caution. Many people believe that AI offers great opportunities for personalized learning, making administrative tasks easier and bringing new ways to teach. However, there are still worries about privacy, fairness and the possibility of replacing traditional teaching jobs. A study by the Digital Education Council found that 86% of students admit to using AI in their studies.  This paper explores the positive and negative educational effects of higher education students using AI tools in learning. As AI becomes increasingly integrated into educational settings, stakeholders must understand both the potential benefits and the challenges it poses. Drawing on recent literature, surveys, and case studies, this research identifies key advantages such as personalized learning and administrative efficiency and significant disadvantages, including academic integrity concerns and the stop of human thinking and creativity. Recommendations for policy and practice are offered.
Keywords: Artificial Intelligence, higher education, advantages, disadvantages